Present-day stresses in Brunei, NWBorneo: superposition of deltaic and active margin tectonics - King, R.; Hillis, R.; Tingay, Mark; Damit, A. (Blackwell Publishing Ltd, 2009)
The Baram Delta System, Brunei, NW Borneo, is a Tertiary delta system located on an active continental margin. Delta top regions in many Tertiary delta systems (e.g. Niger Delta) are thought to exhibit a normal-fault stress regime and margin-parallel maximum horizontal stress orientations. However, unlike in passive margin Tertiary delta systems, two present-day stress provinces have been previously identified across the Baram Delta System: an inner shelf inverted province with a margin-normal (NW-SE) maximum horizontal stress orientation and an outer shelf extension province with a margin-parallel (NE-SW) maximum horizontal stress orientation. Before this study, there were few data constraining the inverted province other than in the vicinity of the Champion Fields. New data from 12 petroleum wells in the western inner shelf and onshore west Brunei presented herein confirm the margin-normal maximum horizontal stress orientations of the inverted province. A total of 117 borehole breakouts, all documented in shale units, and one drilling-induced tensile fracture (in a sandstone interval) reveal a mean maximum horizontal stress orientation of 117 with a standard deviation of 19°. This orientation is consistent with contemporary margin-normal maximum horizontal stress orientations of the inverted province described previously in the vicinity of the Champion Fields that have been linked to basement tectonics of the Crocker-Rajang accretionary complex and associated active margin. However, stress magnitudes calculated using data from these 12 petroleum wells indicate a borderline strik-slip fault to normal fault stress regime for the present day; combined with the absence of seismicity, this suggests that the studied part of the NW Borneo continental margin is currently tectonically quiescent.